RESEARCH OF CONDITIONS DFB LASER ON NEMATIC LIQUID CRYSTALS - Ільчишин, І. П.; Маслов, П. Ю. (Science-based technologies, 2009)
The laser’s terms realization with the distributed feedback (DFB) based on nematic liquid crystal (NLC) at two schemas of excitation are studied. The narrow lasing line on a background the spectrum of hunting oscillation in scheme with a mirror cell are obtained, that testifies to presence DFB. It was analyzed the scheme’s of excitation ways of optimization and characteristics of active layers for the selection narrow lasing line of the DFB-laser.